Penerapan Strategi College Ball untuk Meningkatkan Aktivitas dan Pemahaman Konsep Peserta Didik pada Pembelajaran Matematika Pokok Bahasan Turunan Fungsi Kelas XI di MA Darul Irfan - Jaka Wijaya Kusuma; Maulida Nur; Anisa Dwi Safitri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Mathematics is the science of logic about form, arrangement, quantity, concepts that relate to one another in large numbers. In learning mathematics, requiring the right learning strategy is not easy, there are factors that must be considered, one of which is the quality of individuals in one class. One of the right and fun strategies is to use a college ball learning strategy. The aims of this research are 1). To find out whether the increase in the ability to understand the concepts of students who are given learning with the college ball strategy is better than those given conventional learning, 2). To find out how the activities of students after being given learning with the college ball strategy. This research was conducted in class XI MA Darul Irfan, with a total sample of 65 people, the population was taken from class XI A 33 students and class XI B 32 students. Data collection techniques by conducting observations, documentation and questions. Meanwhile, the data analysis used descriptive statistical analysis and inferential statistical analysis with t-test and activity sheets. The results of this study are the N-gain of the experimental class is 0.7601 with a high category while the N-gain of the control class is 0.4124 with the medium category and has an increase in student activity reaching a percentage of 73.03% with the criteria "active". Then it can be concluded 1). There is an increase in the level of understanding of the concept of students who are given college ball strategy learning better than those given conventional learning, 2) after doing college ball strategy learning there are changes in activities in student learning such as active students asking questions and expressing opinions, active discussions in groups, can solve problems during discussion, and dare to answer questions.